Bispecific Antibodies for IFN-β Delivery to ErbB2+ Tumors - Vladislav S. Rybchenko; Anna A. Panina; Teimur K. Aliev; Olga N. Solopova; Dmitry S. Balabashin; Valery N. Novoseletsky; Dmitry A. Dolgikh; Petr G. Sveshnikov; Mikhail P. Kirpichnikov (Biomolecules, 2021)
The main aim of our work was to create a full-length bispecific antibody (BsAb) as a vehicle for the targeted delivery of interferon-beta (IFN-β) to ErbB2+ tumor cells in the form of non-covalent complex of BsAb and IFN-β. Such a construct is a CrossMab-type BsAb, consisting of an ErbB2-recognizing trastuzumab moiety, a part of chimeric antibody to IFN-β, and human IgG1 Fc domain carrying knob-into-hole amino acid substitutions necessary for the proper assembly of bispecific molecules. The IFN-β- recognizing arm of BsAb not only forms a complex with the cytokine but neutralizes its activity, thus providing a mechanism to avoid the side effects of the systemic action of IFN-β by blocking IFN-β Interaction with cell receptors in the process of cytokine delivery to tumor sites. Enzyme sandwich immunoassay confirmed the ability of BsAb to bind to human IFN-β comparable to that of the parental chimeric mAb. The BsAb binds to the recombinant ErbB2 receptor, as well as to lysates of ErbB2+ tumor cell lines. The inhibition of the antiproliferative effect of IFN-β by BsAb (IC50 = 49,3 µg/mL) was demonstrated on the HT29 cell line. It can be proposed that the BsAb obtained can serve as a component of the immunocytokine complex for the delivery of IFN-β to ErbB2-associated tumor cells.